The influence of total quality management (TQM) and iso 9001 certification on customer satisfaction with service quality as an intervening variable at PT. Paramatech Indonesia - Agustina Agustina; Muchsin Saggaff Shihab (Jurnal Scientia, 2024)
The proliferation of companies in the field of labor supply or outsourcing services has resulted in business competition in grabbing customer attention.Companies operating in the service sector must ensure that their customers are satisfied with the products and services provided. Therefore, PT. Paramatech Indonesia must have good quality so that its target customers feel satisfied and increase customer satisfaction with the services offered. One way to achieve this is by implementing the concept of total quality management (TQM) and obtaining ISO 9001 certification. The aim of this research was to determine the effect of total quality management (TQM) and ISO 9001 certification on customer satisfaction with service quality as an intervening variable at PT. Paramatech Indonesia. This research used quantitative research methods. The sample in this study was 88 respondents who were all customers in the last year and were selected using a sampling method, namely purposive sampling with judgment sampling from the PT. Paramatech Indonesia customer database in accordance with the research objectives. In this research, hypothesis testing was carried out using a structural equation modeling (SEM) approach based on partial least squares (PLS) or shortened to SEM-PLS. Each hypothesis was analysed using the SmartPLS application version 4.0.9.9 to test the relationship between variables. The results of this research show that total quality management (TQM) has a negative but not significant effect on customer satisfaction at PT. Paramatech Indonesia, ISO 9001 certification has a positive and significant effect on customer satisfaction at PT. Paramatech Indonesia, total quality management (TQM) and ISO 9001 have a synergistic effect on customer satisfaction at PT. Paramatech Indonesia, as well as there is a role for service quality in the relationship between total quality management (TQM) and ISO 9001 certification on customer satisfaction at PT. Paramatech Indonesia. The limitations of this research are limited time and variables, so the results of this research cannot yet be used as a picture of actual conditions in companies in Indonesia.